College Algebra 7th Edition

Published by Brooks Cole
ISBN 10: 1305115546
ISBN 13: 978-1-30511-554-5

Chapter P, Prerequisites - Chapter P Review - Exercises - Page 77: 74



Work Step by Step

Use the formula $(a+b)^3 = a^3 + 3a^2b+3ab^2+b^3$ with $a=2x$ and $b=1$ to obtain: $(2x+1)^3 \\=(2x)^3 + 3(2x)^2(1) + 3(2x)(1^2) + 1^3 \\=8x^3+3(4x^2) + 6x(1)+1 \\=8x^3+12x^2+6x+1$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.